Functional social support within a medical supervised outpatient treatment program - Mutschler, Jochen; Eisenacher, Sarah; Dirican, Gülseren; Großhans, Martin; Kiefer, Falk (The American journal of drug and alcohol abuse, 2013)
Background: This study examined functional social support (FSS) and its impact on treatment outcome in alcohol-dependent outpatients treated with supervised disulfiram. Method: FSS was assessed cross-sectionally in 46 severe alcohol-dependent patients participating in a close-meshed biopsychosocial treatment program. The FSS was measured with the Medical Outcome Study Social Support Survey. Results: We found significantly higher FSS levels in patients with a current partnership. No significant influence was found of the FSS on days until relapse and retention time. However, FSS was positively correlated with cumulative abstinence. In comparison with another patient sample, it can be shown that the patients of the close-meshed biopsychosocial treatment program seemed to perceive more FSS, presumably through the higher frequency of the outpatient treatment contacts. Conclusion: High FSS is associated with a current partnership and with a higher cumulative time of abstinence through close professional supervision. A better understanding of the underlying mechanisms of social relationships in alcohol-dependent patients would probably help to improve treatment outcome in the future.